Pengaruh Motivasi dan Kemampuan terhadap Prestasi Kerja Pegawai Dinas Pendidikkan Pemerintah Kota Batu - Hermawati, Adya (DINAMIKA DOTCOM, 2012)
This research aims: 1) to determine the influence of motivation and ability variables simultaneously on employee job performance, 2) to determine the influence of motivation and ability variables partially on employee job performance, and 3) to determine which of the variables that have the motivation and ability of dominant influence the performance of the employees at the Department of Education City of Stone. The hypothesis of this study were 1) variable motivation and the ability to simultaneously influence the performance of the employee, 2) variable motivation and ability to partially affect the performance of the employee, 3) the dominant variables affect the ability of the employees work performance at the Rock City Department of Education.Research states that motivation and the ability to simultaneously influence the achievement of Education Office of Labor officials Stone. Then the motivation and ability to partially affect the Performance Work Education Department officials Stone. Furthermore Ability dominant influence employee Achievement Education Department Stone. Keywords: Motivation, Ability, Performance Work